Randomized controlled trial comparing impact on platelet reactivity of twice-daily with once-daily aspirin in people with Type 2 diabetes - Bethel, M. A.; Harrison, P.; Sourij, H.; Sun, Y.; Tucker, L.; Kennedy, I.; White, S.; Hill, L.; Oulhaj, A.; Coleman, R. L.; Holman, R. R. (Diabetic medicine, 2016)
Aims Reduced aspirin efficacy has been demonstrated in people with Type 2 diabetes. Because increased platelet reactivity and/or turnover are postulated mechanisms, we examined whether higher and/or more frequent aspirin dosing might reduce platelet reactivity more effectively. Methods Participants with Type 2 diabetes (n = 24) but without known cardiovascular disease were randomized in a three‐way crossover design to 2‐week treatment periods with aspirin 100 mg once daily, 200 mg once daily or 100 mg twice daily. The primary outcome was platelet reactivity, assessed using the VerifyNow™ ASA method. Relationships between platelet reactivity and aspirin dosing were examined using generalized linear mixed models with random subject effects. Results Platelet reactivity decreased from baseline with all doses of aspirin. Modelled platelet reactivity was more effectively reduced with aspirin 100 mg twice daily vs. 100 mg once daily, but not vs. 200 mg once daily. Aspirin 200 mg once daily did not differ from 100 mg once daily. Aspirin 100 mg twice daily was also more effective than once daily as measured by collagen/epinephrine‐stimulated platelet aggregation and urinary thromboxane levels, with a similar trend measured by serum thromboxane levels. No episodes of bleeding occurred. Conclusions In Type 2 diabetes, aspirin 100 mg twice daily reduced platelet reactivity more effectively than 100 mg once daily, and numerically more than 200 mg once daily. Clinical outcome trials evaluating primary cardiovascular disease prevention with aspirin in Type 2 diabetes may need to consider using a more frequent dosing schedule. What's new? Aspirin is an established intervention for the secondary prevention of cardiovascular disease, but has a relative lack of efficacy for primary prevention of cardiovascular disease in people with diabetes. This study demonstrates that aspirin 100 mg given twice daily was more effective in reducing platelet reactivity than 100 mg given once daily. These data should help inform the design of future large‐scale trials evaluating the potential risks and benefits of aspirin for primary cardiovascular prevention in people with Type 2 diabetes.